A S4N4-like [Co4(μ-Cl)4] based metal–organic framework with sum topology and selective CO2 uptake. Issue 47 (21st November 2016) - Liu, Huiyan; Meng, Fei; Lu, Zhiyong; Bai, Junfeng
Abstract : A novel sum -type metal–organic framework based upon S4 N4 -like [Co4 (μ-Cl)4 ] clusters, NJU-Bai18, was synthesized with high and selective CO2 uptake. Abstract : A metal–organic framework, [Co4 (μ-Cl)4 (DPB)4 ]·6DMF·8H2 O (NJU-Bai18; NJU-Bai for Nanjing University Bai's group) (HDPB = 3, 5-di(pyridin-4-yl)benzoic acid), with (3, 12)-connected sum topology was presented, which is the first MOF based upon the S4 N4 -like [Co4 (μ-Cl)4 ] cluster and exhibits high CO2 uptake (20.0 wt% at 1 bar) and high selectivity to CO2 /N2 (27.5) at 273 K.